CircRNAs in cancer metabolism: a review - Yu, Tao; Wang, Yanfen; Fan, Yu; Fang, Na; Wang, Tongshan; Xu, Tongpeng; Shu, Yongqian (Journal of hematology and oncology, 2019)
Altered energy metabolism is a hallmark of tumors aiming at supplying necessary nutrients for tumorigenesis and development. These redirected metabolic pathways associated with carbohydrate, lipid and amino acid are orchestrated not only by carcinogenic proteins but by non-coding RNAs. Among them, circular RNA (circRNA), as a kind of novel identified non-coding RNAs, has become the focus of attention. Through binding with corresponding microRNAs or directly contacting proteins, circRNA plays a primarily important role in regulating cellular metabolism. Herein, we analyze the emerging findings and select circRNAs contributing to mutant glycolysis, lipogenesis and lipolysis, glutam inolysis, and oxidative respiration to deepen the understanding about the cancer metabolic regulatory network. In addition, we also discuss the possibility of circRNAs exerting their functions via exosomes and cancer stem cells. Owing to their unique structures and wide impacts, circRNAs may help reap huge fruits in developing clinical treatments targeting cancer metabolism.